Endophyte-mediated enhancement of salt resistance in Arachis hypogaea L. by regulation of osmotic stress and plant defense-related genes - Liang, Qihua; Tan, Dedong; Chen, Haohai; Guo, Xiaoli; Afzal, Muhammad; Wang, Xiaolin; Tan, Zhiyuan; Peng, Guixiang (Frontiers in Microbiology, 2024)
Introduction: Soil salinization poses a significant environmental challenge affecting plant growth and agricultural sustainability. This study explores the potential of salt-tolerant endophytes to mitigate the adverse effects of soil salinization, emphasizing their impact on the development and resistance of Arachis hypogaea L. (peanuts). Methods: The diversity of culturable plant endophytic bacteria associated with Miscanthus lutarioriparius was investigated. The study focused on the effects of Bacillus tequilensis, Staphylococcus epidermidis, and Bacillus siamensis on the development and germination of A. hypogaea seeds in pots subjected to high NaCl concentrations (200 mM L -1 ). Results: Under elevated NaCl concentrations, the inoculation of endophytes significantly (p < 0.05) enhanced seedling germination and increased the activities of enzymes such as Superoxide dismutase, catalase, and polyphenol oxidase, while reducing malondialdehyde and peroxidase levels. Additionally, endophyte inoculation resulted in increased root surface area, plant height, biomass contents, and leaf surface area of peanuts under NaCl stress. Transcriptome data revealed an augmented defence and resistance response induced by the applied endophyte (B. tequilensis, S. epidermidis, and B. siamensis) strain, including upregulation of abiotic stress related mechanisms such as fat metabolism, hormones, and glycosyl inositol phosphorylceramide (Na + receptor). Na + receptor under salt stress gate Ca 2+ influx channels in plants. Notably, the synthesis of secondary metabolites, especially genes related to terpene and phenylpropanoid pathways, was highly regulated. Conclusion: The inoculated endophytes played a possible role in enhancing salt tolerance in peanuts. Future investigations should explore protein-protein interactions between plants and endophytes to unravel the mechanisms underlying endophyte-mediated salt resistance in plants.